Analisis Surveilans Gizi : Peningkatan Obesitas Anak Dan Balita Indonesia Periode 2014-2024 - Aulia Natasya; Fadillah Faturrahman; Isaac Avicenna Abdalla; Laila Deswanti Kurniasari; Muhammad Fahmi Hasan; Naura Zamdiya Azzahra; Sugeng Wiyono; Zaskia Mutiara Anduta (CV. Multi Kreasi Media, 2026)
Childhood obesity in Indonesia is rising due to nutritional transition and sedentary lifestyles. This study aims to analyze obesity trends in children and toddlers (2014–2024) and their contributing factors. The method of this research is a descriptive literature review using secondary data (Riskesdas, BPS, UNICEF) via purposive sampling. The results of this study indicate that prevalence is fluctuating, rising from 1.6% (2015) to a peak of 8% (2018), and eventually reaching 3.4% (2024). Key drivers include high-energy food intake, physical inactivity due to gadgets, and parenting styles. From this study it can be concluded that Strengthening nutritional surveillance and community-based interventions through Posyandu and families is vital for sustainable obesity control.